2019
DOI: 10.54987/jemat.v7i1.464
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Molybdate-reducing Enterobacter cloacae from Agricultural Soil in Gwale LGA Kano State, Nigeria

Abstract: Agricultural and industrial activities contribute most to the pollutants found globally; therefore, bioremediation of these pollutants is intensely sought. This research isolated a molybdenum-reducing bacterium from agricultural soil. The bacterium grown in low phosphate media (LPM) reduces molybadate to Mo-blue optimally at pH between 6.5 and 7.0, temperature between 35 and 40 °C, glucose at 5 g/L and glycine at 3 g/L were the best electron donor and nitrogen sources, respectively. The optimum molybdate conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Solid medium was prepared by the addition of 18 g agar per L of medium. The Mo-reducing bacterium used in this study was previously isolated and identified as Enterobacter cloacae [22].…”
Section: Methodsmentioning
confidence: 99%
“…Solid medium was prepared by the addition of 18 g agar per L of medium. The Mo-reducing bacterium used in this study was previously isolated and identified as Enterobacter cloacae [22].…”
Section: Methodsmentioning
confidence: 99%
“…It is vital to determine the amounts of phosphate and molybdate that enable effective molybdenum reduction since it has been demonstrated that both phosphate and molybdate hinder the synthesis of molybdenum blue in bacteria [24,25,[27][28][29][30][31][32][33][34][35][36][37][38]49,[52][53][54][55][56][57]. Phosphate was shown to be most effective at a concentration of 5 millimoles per liter (mM), with greater quantities being highly reduction-inhibitory (Fig.…”
Section: Reduction At Various Phosphate and Molybdate Concentrationsmentioning
confidence: 99%
“…For optimum reduction, each and every molybdenumreducing bacteria that has been discovered up to this point requires a phosphate concentration of no more than 5 mM [24,25,[27][28][29][30][31][32][33][34][35][36][37][38]49,[52][53][54][55][56][57]. According to research conducted on how the concentration of molybdenum affected the process of molybdenum reduction, the newly isolated bacterium tolerate and reduce molybdenum even at 60 mM, but at the expense of a reduction in Mo-blue synthesis.…”
Section: Reduction At Various Phosphate and Molybdate Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…At levels of several parts per million, molybdenum is very poisonous to ruminants, with cows is by far the most impacted [3,4]. A variety of Mo-reducing bacteria have been isolated to date, and several of these bacteria have also been locally identified [5][6][7][8][9][10][11][12]12,13] and several international strains from Egypt, Indonesia, Pakistan and Nigeria [14][15][16][17][18][19][20][21][22][23][24][25] and Antarctica [26][27][28]. In contrast with other heavy metals such as arsenic, selenium and chromium, the presumed low toxicity of molybdenum to humans and other animals has resulted in not many works as a detoxification procedure on molybdenum reduction.…”
Section: Introductionmentioning
confidence: 99%